Trends in emergency department visits due to back pain and spine surgeries during the COVID-19 pandemic in Finland - Saara Jäntti, BM; Ville Ponkilainen, MD, PhD; Heikki Mäntymäki, MD, PhD; Mikko Uimonen, MD; Ilari Kuitunen, MD, PhD; Ville M. Mattila, MD, PhD (Medicine, 2022)
Abstract. We aim to report the incidences of ED visits due to back pain, hospitalizations, and urgent spine surgeries during the first and second waves of COVID-19 in Finland. The number of emergency department visits and hospitalizations due to back pain as well as urgent spine surgeries in the adult population was collected from hospital discharge registers for the years 2017 through 2019 (reference years) and 2020. This study was conducted at three large Finnish hospitals. The monthly incidence with 95% confidence intervals (CI) of emergency department visits and hospitalizations due to back pain and spine surgeries in the three participating hospitals were calculated and compared by incidence rate ratios (IRR). Visits to ED due to back pain decreased during the pandemic. The incidence of ED visits due to back pain was similar in February (IRR 0.95, CI: 0.82-1.10), but a decrease was seen after lockdown began (March IRR 0.67, CI: 0.57-0.78; April IRR 0.65, CI: 0.56-0.76) compared to the reference years. A second decrease in visits was seen after regional restrictions were implemented in October (IRR 0.88, CI: 0.76-1.02). The most common diagnoses were non-specific back pain, lumbar disk herniation, and back contusion. Incidence of non-specific back pain decreased during the lockdown (March IRR 0.65, CI: 0.55-0.78) and regional restrictions (October IRR 0.83, CI: 0.70-0.98), whereas the rates of other diagnoses remained unchanged, and incidences of hospitalizations and urgent spine surgeries remained stable. A clear decrease in ED visits due to back pain was seen during the first and second waves of the pandemic. This decrease was mainly the result of patients with non-specific back pain avoiding visits to the ED. The incidence of specific back pain, hospitalizations, and urgent spine surgeries remained unchanged during the pandemic.